Changes to the work-family interface during the COVID-19 pandemic: Examining predictors and implications using latent transition analysis - Vaziri, Hoda; Casper, Wendy J; Wayne, Julie Holliday; Matthews, Russell A (Journal of applied psychology, 2020)
Employees around the world have experienced sudden, significant changes in their work and family roles due to the COVID-19 pandemic. However, applied psychologists have limited understanding of how employee experiences of work-family conflict and enrichment have been affected by this event and what organizations can do to ensure better employee functioning during such societal crises. Adopting a person-centered approach, we examine transitions in employees' work-family interfaces from before COVID-19 to after its onset. First, in Study 1, using latent profile analysis (N = 379; nonpandemic data), we identify profiles of bidirectional conflict and enrichment, including beneficial (low conflict and high enrichment), active (medium conflict and enrichment), and passive (low conflict and enrichment). In Study 2, with data collected before and during the COVID-19 pandemic, we replicate Study 1 profiles and explore whether employees transition between work-family profiles during the pandemic. Results suggest that although many remain in prepandemic profiles, positive (from active/passive to beneficial) and negative (from beneficial to active/passive) transitions occurred for a meaningful proportion of respondents. People were more likely to go through negative transitions if they had high segmentation preferences, engaged in emotion-focused coping, experienced higher technostress, and had less compassionate supervisors. In turn, negative transitions were associated with negative employee consequences during the pandemic (e.g., lower job satisfaction and job performance, and higher turnover intent). We discuss implications for future research and for managing during societal crises, both present and future. (PsycInfo Database Record (c) 2020 APA, all rights reserved).